Role of neutrophils in the pathogenesis of Post Kala-azar Dermal Leishmaniasis (PKDL). - Madhurima Roy; Ritika Sengupta; Bidhan Chandra Chakraborty; Uttara Chatterjee; Esther von Stebut; Paul M Kaye; Mitali Chatterjee (Public Library of Science (PLoS), 2024)
Background Post Kala-azar Dermal Leishmaniasis (PKDL) is a dermal sequel of visceral leishmaniasis (VL), poses a significant threat to the success of ongoing kala-azar elimination program, due to its potential role in sustaining transmission cycles and complicating disease management strategies. In VL, neutrophils have been identified as the 'first line of defence', having multiple roles in disease pathogenesis, but their role in PKDL, if any, still remains elusive; presenting a critical gap in knowledge, and was the aim of this study. Methodology/principal findings In a cohort of PKDL patients, CD66b+ neutrophils were quantified in skin biopsies, followed by immunostaining of FFPE sections to identify activated neutrophils (CD66b+/CD64+) and degranulated (CD66b+/MPO+), along with expression of neutrophil elastase (NE), matrix metalloprotease 9 (MMP9) and collagen I. Plasma levels of neutrophil chemo-attractants CXCL8/1/2/5, CCL2 and 20 and cytokines, (IL-6, IFN-γ, IL-4, IL-10, TNF-α, IL-17 and IL-22, 23) were evaluated by a multiplex assay, while lesional expression of IL-8, IL-10 and IL-17 was evaluated by immunohistochemistry. As compared to healthy individuals (control skin samples), PKDL cases at the lesional sites had an increased number of activated CD66b+ neutrophils (positive for CD64+, MPO+ and NE+). The plasma levels of neutrophil chemo-attractants, pro-inflammatory and regulatory cytokines were raised as was circulating and lesional IL-8, along with an enhanced lesional expression of IL-10 and IL-17A. An increase in circulatory and lesional MMP9 was accompanied by decreased collagen I, suggesting disintegration of matrix integrity. Conclusions/significance Taken together, in PKDL, activated neutrophils possibly contribute towards modulating the lesional landscape. Understanding this involvement of neutrophils in patients with PKDL, particularly in the absence of an animal model, could offer better understanding of the disease pathogenesis and provide insights into novel therapeutic strategies for the ongoing elimination program.